A new stygobiotic Xiphocaridinella (Crustacea: Decapoda: Atyidae) from the Motena Cave, Samegrelo-Zemo Svaneti region of Georgia, Caucasus - Marin, Ivan (Zootaxa, 2019)
A new stygobiotic atyid shrimp from the genus Xiphocaridinella Sadowsky, 1930 (Crustacea: Decapoda: Atyidae) is described based on morphology and DNA analysis from an underground lake inside the Motena Cave (Martvili Municipality, Samegrelo-Zemo Svaneti, Western Georgia, Caucasus). The new species is genetically well isolated from the West Georgian relatives and clearly differs from the other Caucasian congeners by specific lanceolate unarmed rostrum, turned forward, and by long fingers of pereiopod I and II in both males and females.